PENGARUH PEMBERIAN SWD DAN TENS TERHADAP PENURUNAN NYERI KNEE PADA PENDERITA OA KNEE JOINT DI RS.BHAYANGKARA - Tiar Erawan; Anshar Anshar (Politeknik Kesehatan Makassar, 2020)
Osteoarthritis is the most common type of arthritis and is found specifically in elderly people and is the most common in the world. The population of osteoarthritis sufferers in Indonesia was 34.3 million people in 2002 and reached 36.5 million people in 2007. An estimated 40 % of the population aged over 70 years suffer from osteoarthritis, and 80% of osteoarthritis patients have limited range of motion in various degrees from mild to severe which results in reduced quality of life due to the high prevalence.This research is a pre-experimental study with a one group pre test – post test research design. The research aims to determine the effect of giving SWD and TENS modalities on changes in pain reduction in patients with knee joint OA. This research was carried out at the Physiotherapy Clinic of the Hospital. Bhayangkara Makassar in 25 May – 25 June 2015. The sampling technique used purposive sampling, namely samples that match the inclusion criteria, from this technique 10 samples were obtained.Based on the results of the study, it was shown that the administration of SWD and TENS can produce changes in pain intensity from pre-test to post-test, with an average reduction of 1.3. Administration of SWD and TENS modalities can provide significant differences or changes in pain in knee joint pain with a level significant by 0.000 (p value <0.05).Thus, it can be concluded that the administration of SWD and TENS can produce a significant reduction in pain in patients with knee OA. It is suggested to physiotherapists in hospitals and practice areas to be able to use SWD and TENS, which can provide other methods of treating knee joint OA to reduce significant pain. Keywords: SWD, TENS, pain reduction, Osteortritis, Knee Joint.